Elements of neural networks technology for analyzing the attitude of Twitter users towards brands - Жуланова, Ольга; Ващіліна, Олена Валеріївна (Київський національний університет імені Тараса Шевченка, 2023)
Background. The article is devoted to the issues of effective organization of collection and information analysis about the attitude of Twitter users to brands in the software application form. Issues such as research into modern means of collecting and analyzing information are considered; definition of the functionality that the application should implement; analysis of architectural solutions and selection of software necessary for its implementation. Methods. When conducting research, marketing theory is used in the field of collecting information about consumer opinions, research on methods of information analysis for the purpose of classifying consumer mood, empirical analysis and synthesis of architectures used in the creation and comparison of neural network models for text classification, development and construction of own model for classification. Results. As part of the task of software implementation of tweet text analysis, the architecture of convolutional and recurrent neural networks was investigated, a comparison of various hyper parameter values of neural networks was made, in particular, activation functions, loss functions, the number of learning epochs, the number of network layers, a comparison of different Python libraries for processing natural languages in the context of tweet evaluation. Сonclusions. The practical significance of the study is the creation of a software tool for effective analysis of Twitter users’ attitudes towards brands, which can serve to improve the effectiveness of marketing activities of brands.

В с т у п . Висвітлено проблему ефективної організації збору й аналізу інформації про ставлення користувачів мережі "Твітер" до брендів у формі програмного застосунку. Розглянуто проблеми дослідження сучасних засобів збору й аналізу інформації; визначення функціоналу, який має реалізовувати застосунок; аналізу архітектурних рішень і вибору програмних засобів, необхідних для його реалізації. М е т о д и . У процесі досліджень застосовано теорію маркетингу у сфері збору інформації про висновки споживачів, досліджено методи аналізу інформації з метою класифікації настрою споживачів, емпіричний аналіз і синтез архітектур, що застосовувався у створенні й порівнянні моделей нейронних мереж для класифікації тексту, розроблення та побудови власної моделі для класифікації. Р е з у л ь т а т и . У межах задачі програмної реалізації аналізу тексту твітів досліджено архітектуру згорткових і рекурентних нейронних мереж, здійснено порівняння різних значень гіперпараметрів нейронних мереж, зокрема і функцій активації, функцій втрат, кількості епох навчання, кількості шарів мережі, виконано порівняння різних Pythonбібліотек для оброблення природної мови в контексті оцінювання твітів. В и с н о в к и . Практичне значення дослідження полягає у створенні програмного засобу для ефективного аналізу ставлення користувачів мережі "Твітер" до брендів, який може слугувати для підвищення ефективності маркетингової діяльності брендів.
Елементи нейромережної технології аналізу ставлення користувачів Twitter до брендів
Keywords: Twitter; аналіз інформації; класифікація тексту; сентиментальний аналіз; нейронні мережі; програмний застосунок; бібліотеки Python; Twitter; information analysis; text classification; sentiment analysis; neural networks; software application; Python libraries